Factors related to cycling performance - Naukkarinen, V. (University of North Texas, 2001)
There were two primary goals in this investigation. The first goal was to determine if results from field tests (time-trials and a Conconi incremental test) are related to performance in mass-start long-distance bicycle races. The second goal was to investigate inter-relationships among field test variables. The testing variables measured were critical velocity (CV), Conconi anaerobic threshold (AT) velocity, 4mM AT velocity, fatigue index, peak blood lactate, and anaerobic work capacity. Participants were USCF 30 category 1 through 5 cyclists. Participants performed one 20.75 km and two 10.37 km all-out tests in the field. They also performed an incremental test. The tests were performed at one-week intervals. Results from the field tests were compared to recent mass-start racing performance. Results indicated that Conconi AT velocity was related to performance in a 161-km race. There was also a relationship between 4mM AT velocity and CV and between Conconi AT velocity and 4mM AT velocity. It was concluded that field tests might provide information about performance ability in mass-start long-distance bicycle races.